2004
DOI: 10.1103/physrevlett.93.026805
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Core-Level Binding-Energy Shifts: The Role of Lattice Strain

Abstract: Our combined experimental and theoretical analysis of the shifts, with particle size, of core-level binding energies (BE's) of metal nanoparticles on insulating supports, shows that these shifts have an important initial state contribution arising, in large part, because of lattice strain. This contribution of BE shifts has not been recognized previously. Lattice strain changes the chemical bonding between the metal atoms and this change induces BE shifts. DOI: 10.1103/PhysRevLett.93.026805 PACS numbers: 73.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
176
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(200 citation statements)
references
References 28 publications
22
176
1
1
Order By: Relevance
“…The quantum confinement effect as well as the lattice strain, and hence the coordination number reduction, is reported to induce the binding energy shifts. 1,9 It is interesting to note that the effects due to quantum confinement have larger dependence on particle size ͑ϳR −2 ͒ than those due to coordination reduction ͑ϳR −1 ͒. 17,18 Indicating that the inner core electrons are more strongly affected by the quantum confinement, the valence electrons are strongly affected by the coordination reduction.…”
Section: -mentioning
confidence: 99%
See 3 more Smart Citations
“…The quantum confinement effect as well as the lattice strain, and hence the coordination number reduction, is reported to induce the binding energy shifts. 1,9 It is interesting to note that the effects due to quantum confinement have larger dependence on particle size ͑ϳR −2 ͒ than those due to coordination reduction ͑ϳR −1 ͒. 17,18 Indicating that the inner core electrons are more strongly affected by the quantum confinement, the valence electrons are strongly affected by the coordination reduction.…”
Section: -mentioning
confidence: 99%
“…The common observation in the XPS studies of metal nanoparticles reported in the literature ͑Au, Ag, Pd, Pt, Ni, Cu, and Co͒ is the positive core level shift with respect to the bulk values. [1][2][3][4][5][6][7][8][9] In a few studies, shifts in the binding energy of valence band with respect to Fermi level and narrowing of valence band spectra have also been reported. 3,7,8 Although considerable efforts have been focused on elucidating the physical origin of the observed size dependent changes, the interpretation of the observed behavior is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 A small positive shift of the absorption edge compared with pristine MnO@C could be related to the pulverization of the MnO during the charge/discharge process. 37 The radial-structure functions of the Mn K-edge (Figure 8c) Tuning MnO nanowire synthesis seeded by Si particles H Wei et al demonstrate the obvious increase in the peak height at 1.5 angstroms, implying an increase in the ordering of the O 2 À ions in the MnO structure, which induces the fast diffusion of Li ions and a low internal resistance. 38 As for the change in the radial distribution function of the second shell of the MnO@C nanowire, it may be consistent with the increase in the disorder degree of the Mn-Mn shell corresponding to the coordination of the second shell, which was supported by the increases of Debye-Waller factor of Mn-Mn.…”
Section: Electrochemical Properties Of Mno@c Nanowirementioning
confidence: 99%